Banks in transition countries as one of most attractive investments - Silvije Orsag; Lidija Dedi; Emil Mihalina (UTMS Journal of Economics, 2011)
The primary goal of this paper is to analyze the banking sector in transition countries in Central and Eastern Europe, and identify bank's potential as an investment in the globalized environment. The primary hypothesis is that banking sector is one of the most attractive investment areas in transition countries. In the comparison with financial systems of G7 and other growth countries, the financial industry in transition countries shows significant potential for future growth and development. Operating as universal bank with acquired position in financial supervisory bodies banks can easy control and slows down growth and development of nonbanking financial institutions. They are not overly involved in risky operations of securitization and were not so much exposed to the recent crisis. Analysis of the banking sector in transition countries has been made on available sources of secondary data and comparable quantities. Comparable quantities are analyzed with descriptive statistics, starting from the general characteristics of the region and individual countries, through macroeconomic indicator analysis to analysis of assorted indicators of banking sector which have dominant influence on prospective cash flows and risk, i.e key components of bank's value as an investment.
Keywords: 330; banking sector; investments; transition countries; growing potential; crisis